Spectrophotometric Determination of Ramipril and Hydrochlorothiazide in a Mixture - Dinc, Erdal; Baleanu, Dumitru (Asian Journal of Chemistry, 2011)
Double wavelet transforms based on the use of continuous wavelets transform (CWT) and discrete wavelets transform (DWT) were proposed for the simultaneous quantification of hydrochlorothiazide and ramipril in tablets. DMEY-CWT was applied to the simultaneous quantitative resolution of the overlapping spectra of the UV spectra of the related compounds and their two-component mixtures. After that DMEY-CWT spectra were processed by BIOR3.5-DWT due to the noises and fluctuations coming from instrumentation and experimental media, respectively, to obtain the smoothing and denosing double transformed signals. Calibration graphs for ramipril and hydrochlorothiazide were obtained by measuring the double transformed wavelet amplitudes at 254.1 and 246.4 nm in the spectral region 230.0 and 281.1 nm, respectively. The validation of the continuous wavelets transform signal processing method was performed on the recovery study. The proposed method was successfully applied to the commercial tablets containing two compounds and good accuracy and precision were reported.